Cloud native patterns : designing change-tolerant software - Davis, Cornelia (Software developer) (Manning Publications, 2019)
This book fills a gap between theory and practice ... entertaining and educational. From the Foreword by Gene Kim, coauthor of The Phoenix Project Cloud Native Patterns is your guide to developing strong applications that thrive in the dynamic, distributed, virtual world of the cloud. This book presents a mental model for cloud-native applications, along with the patterns, practices, and tooling that set them apart. about the technology Cloud platforms promise the holy grail: near-zero downtime, infinite scalability, short feedback cycles, fault-tolerance, and cost control. But how do you get there? By applying cloudnative designs, developers can build resilient, easily adaptable, web-scale distributed applications that handle massive user traffic and data loads. Learn these fundamental patterns and practices, and you'll be ready to thrive in the dynamic, distributed, virtual world of the cloud. about the book With 25 years of experience under her belt, Cornelia Davis teaches you the practices and patterns that set cloud-native applications apart. With realistic examples and expert advice for working with apps, data, services, routing, and more, she shows you how to design and build software that functions beautifully on modern cloud platforms. As you read, you will start to appreciate that cloud-native computing is more about the how and why rather than the where. what's inside The lifecycle of cloud-native apps Cloud-scale configuration management Zero downtime upgrades, versioned services, and parallel deploys Service discovery and dynamic routing Managing interactions between services, including retries and circuit breakers about the audience Requires basic software design skills and an ability to read Java or a similar language. about the author Cornelia Davis is Vice President of Technology at Pivotal Software. A teacher at heart, she's spent the last 25 years making good software and great software developers. The book's focus on real world challenges makes this an essential manual for modern day projects. David Schmitz, Senacor Technologies Demystifies the process of building self-healing, distributed, and resilient web applications with low operational maintenance. Raveesh Sharma, Stellapps Technologies A direct and definitive guide to cloud native, with real-life experience driving the narrative. A must-read for practicing engineers who want to feel like a native in the cloud. Shanker Janakiraman, Urjanet NARRATED BY SARAH DAWE.